2013
DOI: 10.1002/stem.1406
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Impaired Cell Reprogramming in Nonhomologous End Joining Deficient Cells

Abstract: Although there is an increasing interest in defining the role of DNA damage response mechanisms in cell reprogramming, the relevance of proteins participating in nonhomologous end joining (NHEJ), a major mechanism of DNA double-strand breaks repair, in this process remains to be investigated. Herein, we present data related to the reprogramming of primary mouse embryonic fibroblasts (MEF) from severe combined immunodeficient (Scid) mice defective in DNA-PKcs, a key protein for NHEJ. Reduced numbers of induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…The reverse is also true; reprogramming of cells with restricted developmental potential back to a pluripotent state requires dynamic changes in chromatin organization, histone/DNA modifications and reactivation of a complex transcriptome (Apostolou et al, 2013; Phillips-Cremins et al, 2013; Polo et al, 2012; Wei et al, 2013; Zhang et al, 2013). The expanded roles of DNA repair factors in transcriptional control may explain why inactivation of factors in the NER, HR, NHEJ and Fanconi anemia (FA) repair pathways poses such strong barriers to somatic cell reprogramming by OCT4, SOX2, KLF4 and c-MYC (Fong et al, 2011; Gonzalez et al, 2013; Molina-Estevez et al, 2013; Muller et al, 2012; Takahashi and Yamanaka, 2006). On the other hand, rapid ectopic induction of transcription of a large number of genes by these factors during the initial phase of reprogramming could promote TAM and TAR due to a surge in transcriptional load and replication stress (Helmrich et al, 2012), thus activating a DNA damage response that is prohibitive to the conversion process (Hong et al, 2009; Kawamura et al, 2009; Li et al, 2009; Marion et al, 2009; Utikal et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The reverse is also true; reprogramming of cells with restricted developmental potential back to a pluripotent state requires dynamic changes in chromatin organization, histone/DNA modifications and reactivation of a complex transcriptome (Apostolou et al, 2013; Phillips-Cremins et al, 2013; Polo et al, 2012; Wei et al, 2013; Zhang et al, 2013). The expanded roles of DNA repair factors in transcriptional control may explain why inactivation of factors in the NER, HR, NHEJ and Fanconi anemia (FA) repair pathways poses such strong barriers to somatic cell reprogramming by OCT4, SOX2, KLF4 and c-MYC (Fong et al, 2011; Gonzalez et al, 2013; Molina-Estevez et al, 2013; Muller et al, 2012; Takahashi and Yamanaka, 2006). On the other hand, rapid ectopic induction of transcription of a large number of genes by these factors during the initial phase of reprogramming could promote TAM and TAR due to a surge in transcriptional load and replication stress (Helmrich et al, 2012), thus activating a DNA damage response that is prohibitive to the conversion process (Hong et al, 2009; Kawamura et al, 2009; Li et al, 2009; Marion et al, 2009; Utikal et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the components of HR repair, including BRCA1, BRCA2, and Rad51, are crucial for iPSCs generation, 69 among which Rad51 is required not only for the induced pluripotent stem cells (iPSCs) conversion, but also for the maintenance of pluripotency in embryonic stem cells (ESCs) 70 . Moreover, cells deficient in NHEJ component DNA-PKcs show a decreased efficiency of iPSCs generation 71 . Notably, untreated and irradiated E1A + E1B cells expressed the stem cell factor Nanog.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous studies showing that the preservation of genome integrity is a crucial condition for somatic cell reprogramming and production of iPS cells in human and mouse. [9][10][11] In addition, there is also evidence that DNA damage affects cell cycle progression and compromises development of normal fertilized mouse embryos. 50,51 Our results using SCNT embryos provided further evidence that both cell reprogramming and early embryo development are severely affected when genome integrity is disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that maintenance of genome integrity is critical for production of induced pluripotent stem (iPS) cells in humans and mice, [9][10][11] suggesting that genome integrity may also affect somatic cell reprogramming and development of SCNT embryos. DNA double-stranded breaks (DSBs) are recognized as the most biologically significant genotoxic lesions.…”
Section: Introductionmentioning
confidence: 99%